Study Biopotency of Rambusa (Passiflora foetida L.) Fruit Extract As An Antibacterial for Aeromonas hydrophila - Fatmawati Fatmawati; Agussyarif Hanafie; Siti Aisiah; Ririen Kartika Rini; Olga Olga; Rizka Agustina; Aminah Aminah; Elvina Kartiani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Motile Aeromonad Septicemia (MAS) is a disease affecting freshwater fish and is caused by Aeromonas hydrophila. The control of MAS commonly relies on synthetic drugs and antibiotics. This study aimed to evaluate the biopotential of rambusa (Passiflora foetida L.) fruit extract as an antibacterial agent against A. hydrophila. The antibacterial activity was assessed using the disc diffusion and Minimum Inhibitory Concentration (MIC) methods, supported by qualitative and quantitative phytochemical analyses. The results showed that rambusa fruit extract produced inhibition zones against A. hydrophila. The inhibition zone of the aqueous extract after 24 hours of incubation was 3.25 mm, while the methanolic extract produced an inhibition zone of 11.42 mm. These findings indicate that rambusa fruit extract prepared using both distilled water and methanol as solvents can inhibit the growth of A. hydrophila. Qualitative phytochemical screening of the aqueous extract revealed the presence of flavonoids, alkaloids, tannins, saponins, and hydroquinones based on the 10% KOH test. Quantitative analysis also detected flavonoids, alkaloids, tannins, saponins, steroids, phenolics, anthocyanins, and triterpenoids. The MIC test showed that concentrations of 100–600 mg/L were effective in inhibiting the growth of A. hydrophila within the weak inhibition category, while concentrations of 700–900 ppm showed higher inhibitory activity. These results suggest that rambusa fruit extract has potential as a natural antibacterial agent against A. hydrophila.